La La land [videorecording (DVD)] - Gosling, Ryan, 1980-; Stone, Emma, 1988-; DeWitt, Rosemarie (Lionsgate, 2017)
A jazz pianist falls for an aspiring actress in Los Angeles. This original musical about everyday life explores the joy and pain of pursuing dreams.